Health inequalities in Argentina and Italy : a comparative analysis of the relation between socio-economic and perceived health conditions - Sarti, Simone (2018)
Fil: Sarti, Simone. Universidad de Milán, Departamento de Ciencias Sociales y Políticas; Italia